Absence of internal multidecadal and interdecadal oscillations in climate model simulations - Mann, Michael E.; Steinman, Byron A.; Miller, Sonya K. (Nature communications, 2020)
For several decades the existence of interdecadal and multidecadal internal climate oscillations has been asserted by numerous studies based on analyses of historical observations, paleoclimatic data and climate model simulations. Here we use a combination of observational data and state-of-the-art forced and control climate model simulations to demonstrate the absence of consistent evidence for decadal or longer-term internal oscillatory signals that are distinguishable from climatic noise. Only variability in the interannual range associated with the El Niño/Southern Oscillation is found to be distinguishable from the noise background. A distinct (40–50 year timescale) spectral peak that appears in global surface temperature observations appears to reflect the response of the climate system to both anthropogenic and natural forcing rather than any intrinsic internal oscillation. These findings have implications both for the validity of previous studies attributing certain long-term climate trends to internal low-frequency climate cycles and for the prospect of decadal climate predictability. The existence of regular decadal or longer climate oscillations has been the subject of intensive discussion. Here, statistical analysis of observational data and a large ensemble of model simulations show no evidence for longer-term internal oscillations that are distinguishable from climatic noise.